2020
DOI: 10.1088/1361-6528/abb04f
|View full text |Cite
|
Sign up to set email alerts
|

Graphite films/carbon fiber fabric/ polyurethane composites with ultrahigh in-plane thermal conductivity and enhanced mechanical properties

Abstract: Thermally conductive composites have attracted great attention in virtue of their crucial role in thermal management. In this work, laminated composites were prepared by laying graphite films (GF) and carbon fiber fabrics (CF) in a certain order, then penetrating thermoplastic polyurethane (TPU), finally hot-pressing. In order to enhance the inter-layer strength, the graphite films were perforated with arrays of 1 mm holes in diameter which have intervals of 4 mm and permit the seeping of liquid TPU through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Composites consist of two or more than two materials with different characteristics, and the materials are bonded via physical, chemical, physical-chemical, or mechanical mechanisms. In this study, two types of TPU are combined to form TPU composite films, thereby bettering the tensile performance of the composite films as well as strengthening the adhesion level among laminates [ 22 , 23 , 24 ]. The films can be adjusted according to the thickness and the resulting films exhibit a more even morphology than other films made by molds of various thicknesses via hot pressing.…”
Section: Resultsmentioning
confidence: 99%
“…Composites consist of two or more than two materials with different characteristics, and the materials are bonded via physical, chemical, physical-chemical, or mechanical mechanisms. In this study, two types of TPU are combined to form TPU composite films, thereby bettering the tensile performance of the composite films as well as strengthening the adhesion level among laminates [ 22 , 23 , 24 ]. The films can be adjusted according to the thickness and the resulting films exhibit a more even morphology than other films made by molds of various thicknesses via hot pressing.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the low thermal conductivity of polymer packaging materials, the thermal conductivity of the polymer is usually improved by adding high thermal conductivity fillers. The filler-filled thermal conductive polymer materials are mainly prepared by adding high thermally conductive metal materials (such as copper powder, , silver powder, metal sheet, and wire ), carbon materials (such as carbon fiber, graphene, graphite, carbon nanotube, and carbon black ) or high thermal conductive inorganic fillers (such as aluminum nitride, , boron nitride, silicon nitride, , silicon carbide, magnesium oxide, , silicon oxide, alumina, barium titanate, and zinc oxide) and other high thermal conductivity fillers (such as MXene ). Filler-filled thermal conductive polymer composites have the advantages of a simple preparation method, low cost, suitable types of polymers, and fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the thermal conductivity of most conventional polymeric substrates is very low, in the range of 0.1–0.5 W m −1 K −1 [ 5 ]. Ren et al claimed that the thermal conductivity of laying graphite films/carbon fiber fabrics/TPU composite is up to 242 W m −1 K −1 at room temperature [ 6 ]. In addition, Dong et al reported that the thermal conductivity and thermal stability were also found to be enhanced by introducing carbon black into TPU matrix [ 7 ].…”
Section: Introductionmentioning
confidence: 99%